IMPROVING OF EFL LEARNERSâ SPEAKING PROFICIENCY THROUGH SPEAKING ACTIVITIES INSIDE AND OUTSIDE THE CLASSROOM: A THEORETICAL REVIEW - Syarifuddin, Syarifuddin (LET: Linguistics, Literature and English Teaching Journal, 2012)
In an attempt to improve the learnersâ speaking proficiency in EFL, the demand to teach speaking English is increasing more and more in all levels of education in Indonesia. Many kinds of strategies are applied in teaching and learning process of speaking in order to enable the leaners to perform the microskills and macroskills Â of communication. The widely accepted instructional method in EFL is Communicative Language Teaching which emphasizes Â that the goal of Â language learning is to increase learnersâ communicative competence. The competence Â includes Â Â grammatical competence, Â discourse competence, sociolinguistic competence, and strategic competence as the undrelying abilities of speaking proficiency. Therefore, Â it is the main purpose of this paper to depict the way in which teaching speaking Â should encourage Â learners to engage Â in appropriate speaking Â activities both inside and outside the classroom Â to gain communicative competence. Â Classroom learning is one way to practice and learn speaking, but multitudes of opportunities for learning and practicing speaking exist outside the classroom in English context. Â So, the learners need Â to be encouraged to develop speaking habit and use it in real life communication.